Beberapa Karakteristik Mushaf Kuno Jambi - Syaifuddin, Syaifuddin (SUHUF, 2014)
Before the presence of the printing mechine in the early 19th century, the multiplication of the QurÃ¢â‚¬â„¢an was done through the process of copying manually in many places in Indonesia. As a result of the process of that traditional copying are the happening of some mistakes in the process of copying, the innovation and emergence of various differences among the mushafs. Some research that have been done show that the differences occurred in the aspects of the art of writing (rasm), the sign of reciting, the material of the paper, illuminations and many other aspects to mention. This writing studies six ancient mushafs originated from the province of Jambi. It is through philological and codicological approaches that some characteristics of the Mushaf of Jambi can be clearly identified. Some identification forinstance are the use of the rule of rasm imlÃ„ÂÃ¢â‚¬â„¢i, the variation of waqaf and the rule of reciting the holy Quran (tajwÃ„Â«d), the illumination motifs and the completion of hizb.Keywords:Quran manuscript, rasm Ã¢â‚¬ËœuÃ¡Â¹Â¡mÃ„Âni, rasm imlÃ„ÂÃ¢â‚¬â„¢, ilumination.